Experimental study of supercontinuum generation in step-index highly nonlinear fibres. Issue 15 (2nd September 2021) - Gao, Weiqing; Zhang, Lei; Chen, Haiwen; Li, Jingya; Jiang, Yuxi; Wan, Lipeng; Zhou, Yong; Ma, Xiaohui
Abstract : In this work, supercontinuum (SC) generation in three kinds of step-index highly nonlinear fibres (HNLFs) are experimentally investigated. The generated SC spectra are compared with each other by changing the numbers and wavelengths of the pump sources, and also by employing the HNLFs with different refractive-index differences between the core and the cladding. The widest spectral range of generated SC was about 2650 nm covering from 350 to 3000 nm when using the three pump wavelengths of 800, 1400 and 1867 nm. The results demonstrate that the step-index HNLFs have excellent performances for SC generation and great potentials for the realization of all-fibre SC source.